A Novel Continuous Phase‐Transition Extraction Effectively Improves the Yield and Quality of Finger Citron Essential Oil Extract. (29th October 2020) - Chen, Haiqiang; Yang, Hui; Zhou, Aimei; Xiao, Suyao; Song, Mingyue; Chen, Hanmin; Cao, Yong
Abstract: Citron essential oil contains numerous health‐beneficial components, however, with relatively low level in plants. In this paper, the components and physicochemical properties of finger citron essential oil extract (FEOE) obtained by a novel continuous phase‐transition extraction (CPE) were investigated and compared with those achieved by supercritical fluid extraction (SFE). Results indicated that CPE‐derived FEOE significantly increased by 12% in yield compared to SFE‐derived FEOE. Gas chromatograph ‐ mass spectrometry (GC–MS) analysis showed that FEOE extracted by both methods contained acids, esters, olefins, and alcohols. However, aromatics and heterocycles were only found in CPE‐derived FEOE. Moreover, the relative contents of acids and esters in CPE‐derived FEOEdecreased in comparison with those in SFE‐derived FEOE. On the other hand, the relative contents of olefins, alcohols, aromatic, and heterocycle compounds increased, suggesting a rich and multi‐layered fragrance with plentiful characteristic aroma substances in CPE‐derived FEOE. In addition, FEOE extracted by CPE maintained strong antioxidant activity in a dose‐dependent manner. Together, our results demonstrated that CPE could be a promising technology for essential oil extraction. Abstract :